2000
DOI: 10.1046/j.1365-2893.2000.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic evidence, by multiple clone analysis of hypervariable region 1, for the transmission of hepatitis C virus to chronic haemodialysis patients

Abstract: We analysed hepatitis C virus (HCV) sequences to determine whether nosocomial transmission of HCV occurred in a haemodialysis unit. Twenty patients positive for serum HCV RNA were investigated. All were undergoing haemodialysis therapy in the same room. The hypervariable region 1 (HVR1) sequence of HCV was amplified and multiple clones sequenced. Phylogenetic analysis of these sequences revealed five genetic clusters consisting of HCV isolates from 11 of the 20 patients. In addition to two genetic clusters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Several recent studies [31, 52, 54, 59, 65, 79,143,144,145,146,147,148,149,150] and one large study [44] reported nosocomial patient-to-patient transmission of HCV infection among HD patients performing phylogenetic analysis of HCV viral isolates. Although the potential sources of nosocomial transmission could be dialyzer reuse, internal contamination of HD monitors, and contaminated hands and articles, the two former mechanisms are almost unlikely [92, 93, 151, 152].…”
Section: Evidence Of Nosocomial Transmission and Preventive Strategiesmentioning
confidence: 99%
“…Several recent studies [31, 52, 54, 59, 65, 79,143,144,145,146,147,148,149,150] and one large study [44] reported nosocomial patient-to-patient transmission of HCV infection among HD patients performing phylogenetic analysis of HCV viral isolates. Although the potential sources of nosocomial transmission could be dialyzer reuse, internal contamination of HD monitors, and contaminated hands and articles, the two former mechanisms are almost unlikely [92, 93, 151, 152].…”
Section: Evidence Of Nosocomial Transmission and Preventive Strategiesmentioning
confidence: 99%
“…Nonetheless, the nosocomial transmission of HCV continues to occur (21). Several recent studies provided evidence of patient-to-patient transmission in most of the cases of nosocomial transmission (2, 5, 6, 9, 13, 15-17, 19, 20, 29, 36), although some studies also reported transmission from health care workers to patients and vice versa (10,26,32).In recent years, the use of molecular biology techniques has proven to be a powerful tool in the epidemiological investigation of HCV infection in health care facilities and other settings (2,4,6,9,10,13,15,16,19,20,24,30,32). In particular, phylogenetic tree analysis has often been used to identify the original source of infection.…”
mentioning
confidence: 99%
“…In recent years, the use of molecular biology techniques has proven to be a powerful tool in the epidemiological investigation of HCV infection in health care facilities and other settings (2,4,6,9,10,13,15,16,19,20,24,30,32). In particular, phylogenetic tree analysis has often been used to identify the original source of infection.…”
mentioning
confidence: 99%
“…Recently, a variety of studies have provided, by sequence analysis, reliable molecular evidence for patient-to-patient transmission (Abacioglu et al, 2000;Allander et al, 1994;DeLamballiere et al, 1996;Grethe et al, 2000;Hosokawa et al, 2000;Irish et al, 1999;Izopet et al, 1999;Katsoulidou et al, 1999;LePogam et al, 1998;McLaughlin et al, 1997;Norder et al, 1998), but the exact mode of transmission could not be established. In most cases, breaching or neglecting of hygienic precautions was suspected.…”
Section: Nontransfusional Transmission In Hemodialysis Settingsmentioning
confidence: 99%